INVESTIGATING THE DIFFICULTIES AND STRATEGIES OF THE EFL STUDENTS IN TRANSLATING INDONESIAN ENGLISH TEXT: A CASE STUDY AT ENGLISH DEPARTMENT OF IAIN LANGSA - Muslem Muslem; Syukrina Syukrina; Wahidah Wahidah (Pusat Studi Gender dan Anak, 2021)
This research entitles “Investigating the Difficulties and Strategies of the EFL Students in Translating Indonesian-English Text”. The objectives of this research were to investigate the difficulties experienced by the EFL students at the English Department of IAIN Langsa and to discover the strategies applied by them in the Indonesian-English translation. A qualitative approach was employed as the method of this research and the subjects were involving 10 sixth semester students majoring in English Education at IAIN Langsa. There were two instruments used to gather the data namely test and interview. From the outcomes of the two data, it was acquired that the students had difficulties related to religious vocabularies/terms, grammar, equivalence, and difficulties in assorting the long sentence. Meanwhile, based on the outcomes of the interview were also procured that the students employed three strategies to overcome the difficulties in the text translation, namely 1). Natural Borrowing Strategy, (2). Adaptation Strategy, and (3). Literal Translation Strategy. The students contended that these strategies were appropriate and simple for them to employ it in superintending the problems during the translation process.